Finance and the chemical industry - Marco Da Rin (Fondazione Eni Enrico Mattei (FEEM), 1997)
The paper provides an overview of the financial history of the chemical industry since its inception in the latter half of the nineteenth century in four major countries: Britain, Germany, Japan, and the United States. The chemical industry is particularly intriguing from the point of view of financial economics because of its need to finance large and risky projects with a far-off pay-back horizon. I examine the history of the industry through the allocation and corporate governance attribute of different financial instruments. I explore how cash flow, capital expenditure, R&D intensity, and corporate strategies have been affected by the availability of funds, and the form in which they were provided. At the industry level, I ask how corporate co-ordination, consolidation and restructuring, have been influenced by financial markets. Several points emerge from this detailed empirical analysis. First, the ability to tap diverse sources of external finance has always proved important—and not only at the early stages of a firm's life. Firms which could rely on large cash flows have found it easier to retain their competitive edge. However, availability of capital is not by itself a guarantee of success, as the effectiveness of corporate governance is equally important. Also, the governance features of a financial system change with time, mostly due to changes in regulations. Public policy may then play an important role. Second, the most appropriate type of corporate governance may differ for firms at different stages of maturity. Third, the hallmarks of a country's financial system tend to persist over time, and so their effect on shaping the industry tends to be long lasting. However, in all four countries, the last two decades have witnessed a trend towards deregulation and integration of world securities markets. We should then expect some degree of convergence toward a common pattern.
Keywords: L65; N60; 330; Chemieindustrie; Unternehmensfinanzierung; Betriebliche Finanzwirtschaft; USA; Deutschland; Japan; Großbritannien